(untitled) (Swiss Medical Weekly, 2019)
PURPOSE Extra-abdominal desmoid tumours are benign and rare, and lead to a persistent treatment dilemma because of their high recurrence rate and their heterogeneous behaviour. The goal of this retrospective study was to evaluate the results of different treatment modalities for extra-abdominal desmoid tumours at four sarcoma treatment centres. METHODS The mean follow-up time for the 96 patients included in the study (63.5% female; mean age 38.9 years) was 8.4 years (2.0–40.5 years). The initial treatments were surgery (n = 44), surgery with radiation (n = 16), watchful waiting (n = 15), radiation only (n = 9), or systemic treatment (n = 12). Patient demographics, tumour sites, and the follow-up status of all patients were reviewed and evaluated for each of the treatment modalities. RESULTS The local recurrence rate was 45.5% in patients with primary surgical treatment and 37.5% following surgery combined with irradiation. Patients who were treated with radiation alone showed regressive (33.3%) or stable disease (66.6%). Systemic treatment alone resulted in disease progression in 41.7% of our patients. In the watchful waiting group, 73.3% showed stable disease, 20.0% showed spontaneous regression, and 6.7% showed progression after a mean follow-up of 4.1 years (2.0–11.5 years). CONCLUSIONS Our results suggest that a watchful waiting approach should be the first line treatment in asymptomatic desmoid tumours. However, radiation can help improve local control rates in patients who have undergone surgery. Progression and local recurrence rates following systemic treatment were comparable to those observed in surgery combined with radiation.